2022
DOI: 10.1111/vru.13053
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of renal cortical thickness using ultrasound in normal dogs: a reference range study considering bodyweight and body condition score

Abstract: The renal cortical thickness (RCT) reflects the pathological condition of the kidney, and measuring this parameter can help diagnose renal fibrosis in dogs. The normal reference range of RCT in dogs is broad (3-8 mm) because of the extreme diversity in body size. Therefore, this retrospective, reference interval, and observational design study aimed to establish a normal reference range for RCT in dogs measured using ultrasound by considering bodyweight (BW), body surface area (BSA), body condition score (BCS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
(72 reference statements)
6
14
1
Order By: Relevance
“…In this study, the BW and BW/BCS index were significantly positively correlated with kidney volume, which is consistent with the results of previous studies showing a significantly positive linear relationship between BW, BW/BCS index, and kidney size (32,43,44). In a previous study (32), the BW/BCS index showed a stronger correlation with renal cortical thickness than BW. However, our correlations between kidney volume and BW/BCS index and BW were not significantly different, even though BW had a positive correlation and BCS a negative correlation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the BW and BW/BCS index were significantly positively correlated with kidney volume, which is consistent with the results of previous studies showing a significantly positive linear relationship between BW, BW/BCS index, and kidney size (32,43,44). In a previous study (32), the BW/BCS index showed a stronger correlation with renal cortical thickness than BW. However, our correlations between kidney volume and BW/BCS index and BW were not significantly different, even though BW had a positive correlation and BCS a negative correlation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the BW and BW/BCS index were significantly positively correlated with kidney volume, which is consistent with the results of previous studies showing a significantly positive linear relationship between BW, BW/BCS index, and kidney size ( 32 , 43 , 44 ). In a previous study ( 32 ), the BW/BCS index showed a stronger correlation with renal cortical thickness than BW.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The length of the kidney should be obtained at its greatest dimension in a longitudinal (either sagittal or dorsal) plane 30–31 . Published methods and normal values are available using renal length/aorta or L5/6 measurements, renal cortical thickness, renal cortex to aorta ratios, and cortex/medulla ratios 32–34 . It is the opinion of the panel, however, that these measurements are not necessary to routinely obtain in every patient but can be used when indicated.…”
Section: Examination Of Organ Systemsmentioning
confidence: 99%
“…[30][31] Published methods and normal values are available using renal length/aorta or L5/6 measurements, renal cortical thickness, renal cortex to aorta ratios, and cortex/medulla ratios. [32][33][34] It is the opinion of the panel, however, that these measurements are not necessary to routinely obtain in every patient but can be used when indicated. The shape, cortical echogenicity, and corticomedullary distinction of each kidney should be evaluated and recorded.…”
Section: Urinary Tractmentioning
confidence: 99%